Effective needs anaylsis and functional training principles - Plisk, S. S. (Strength and conditioning for sports performance, 2016)
Athletic preparation has evolved beyond simple fitness- or exertion-oriented training. Many strength and conditioning (S&C) professionals now take a comprehensive `sports performance` approach with their athletes, where movement skill acquisition also gets priority. Such strategies are very productive, but can also be quite challenging, because the practitioner`s competencies must include underpinning scientific knowledge on several fronts, including physiological functions and responses to training, applied anatomy and movement, and principles of training and adaptation. It is also very helpful to apply certain educational strategies to the training process. There are three essential steps involved in preparing any sound strategy, including a training programme: 1. Zero in on the performance target. This gets into the issues of needs analysis and functionality or specificity of training. 2. Assess the current situation. This requires an analysis of athletes` capacity in relation to the performance target, and should also consider their developmental status. 3. Select tactics for achieving generic as well as specific goals and objectives. This gets into the issue of planned variation in means and methods, i.e. periodisation.